Reduction treatment of nickel phyllosilicate supported Pt nanocatalysts determining product selectivity in CO2 hydrogenation. Issue 52 (October 2021) - Song, Miaomiao; Huang, Zhongliang; Chen, Bin; Liu, Sihan; Ullah, Shafqat; Cai, Dongren; Zhan, Guowu
Graphical abstract: Highlights: Catalyst reduction temperature determines CH4 /CO selectivity in CO2 hydrogenation. Metallic Ni active site could be extracted from the Ni phyllosilicate by reduction. NiSiO3 /Pt-500 catalyst reveals a good catalytic performance for CO2 hydrogenation. In-situ DRIFTS suggests metallic Ni 0 inhibits the dissociative adsorption of CO2 . CHx O* intermediate over Ni site is critical to CH4 formation in CO2 hydrogenation. Abstract: Catalyst design is one of the most critical factors in selectively converting CO2 and renewable H2 to value-added chemicals. In this work, Pt nanoparticles with an average size of 2.9 nm were uniformly loaded on hollow mesoporous nickel phyllosilicate which then underwent various reduction treatments to partial extraction of Ni atoms and formation of Ni-Pt bimetallic catalysts for the selective CO2 hydrogenation in a fixed bed reactor. Experimental results reveal that Pt nanoparticles supported on SiO2 are highly selective to CO via reversed water gas shift (RWGS) reaction with 100% CO selectivity, while Pt nanoparticles supported on nickel phyllosilicate show high selectivity for CH4, particularly, under high reduction temperature. By simply changing the reduction temperature or reaction pressure, the production selectivity can be facilely tuned, and the maximum CH4 selectivity achieved in the bimetallic Pt/Ni@phyllosilicate catalyst is 100%. The metallic Ni 0 reduced from nickel phyllosilicate owns a high concentration of Lewis basic sites, which could enhance the adsorption strength of CO2 but prevent the dissociated adsorption. The diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) in different transient states were applied to study the mechanistic insights into how Ni-Pt dual sites tune the product selectivity. The results suggest that CO* over Pt site is the key species for CO2 conversion to CO, whereas the produced CO* could be further hydrogenated to CHx O* intermediate over Ni site, leading to the formation of CH4 . The present work offers a new method to prepare Ni-Pt bimetallic catalysts with excellent CO2 hydrogenation performance towards CH4 .